Performance analysis of pre-sliding motion using sliding mode controller - Kunyahamu, Siti Nur Syazwani (2021)
Friction is typically defined as motion resistance as two surfaces move against each other. In nature and a wide variety of engineering applications, frictional interactions occur between solids. In manufacturing engineering, the friction force is necessary for the machine to prevent sliding. Still, when too much friction is applied to the device, it will affect the device and decrease the positioning and tracking accuracy in mechanical systems. This study identifies friction activity in pre-sliding motion, which is the compensation of friction force at motion reversal. Compensation methods either compensate for the controller (adaptive) or interference forces to achieve improved output in terms of monitoring and contour errors. Sliding Mode Control (SMC) is a design by using MATLAB software to compensate for friction. The Generalized Maxwell-Slip (GMS) friction model is used for numerical analysis. The controller's performance is measured based on reducing the error in the pre-sliding regime after designing the Sliding Mode Controller using Matlab Simulink software. The SMC parameters Lambda (λ), Gain (K) and Delta (ⱷ) were tuned and the best parameters were selected in accordance with the specifications of the configurations suggested, Configuration 1, Configuration 2 and Configuration 3. The lower variability index value, is Configuration 3 which are 0.3456% and the RMSE values is -0.1628, has been found to have the best tuning parameters for the Sliding Mode Control (SMC) controller. Using the best configuration performance that have been chosen, will be used in the PID Controller simulation to view the different output results of two different controllers using the same configuration performance value. The value of variability index and RMSE of PID is 1.9863% and 0.2710. Based on this analyses it shown that the Sliding Mode Controller (SMC) performed well during the simulations as opposed to the PID controller in this study.